2-O-β-D-Glucopyranosyl-L-ascorbic acid, an ascorbic acid derivative isolated from the fruits of Lycium barbarum L., ameliorates high fructose-induced neuroinflammation in mice: involvement of gut microbiota and leaky gut - Wei Dong; Yujia Peng; Guijie Chen; Zhiyong Xie; Weiqi Xu; Wangting Zhou; Jia Mi; Lu Lu; Yi Sun; Xiaoxiong Zeng; Youlong Cao; Yamei Yan (Food Science and Human Wellness)
Western diet (rich in highly refined sugar and fat) can induce a range of metabolic dysfunctions in animals and humans, including neuroinflammation and cognitive function decline. Neuroinflammation and cognitive impairment, two critical pathological characteristics of Alzheimer’s disease, have been closely associated with microbial alteration via the gut-brain axis. Thus, the present study aimed to investigate the influence of 2-O-β-D-glucopyranosyl-L-ascorbic acid (AA-2βG) isolated from the fruits of Lycium barbarum on preventing the high-fructose diet (HFrD) induced neuroinflammation in mice. It was found that AA-2βG prevented HFrD-induced cognitive deficits. AA-2βG also predominantly enhanced the gut barrier integrity, decreased lipopolysaccharide entry into the circulation, which subsequently countered the activation of glial cells and neuroinflammatory response. These beneficial effects were transmissible by horizontal fecal microbiome transplantation, transferring from AA-2βG fed mice to HFrD fed mice. Additionally, AA-2βG exerted neuroprotective effects involving the enrichment of Lactobacillus and Akkermansia, potentially beneficial intestinal bacteria. The present study provided the evidence that AA-2βG could improve indices of cognition and neuroinflammmation via modulating gut dybiosis and preventing leaky gut. As a potential functional food ingredient, AA-2βG may be applied to attenuate neuroinflammation associated with Western-style diets.